MISUNDERSTANDING OF THE INDONESIAN HUMAN RIGHTS ACTIVISTS ON THE APPLICATION OF THE DEATH PENALTY - Arifin, Tajul (Asy-Syari’ah, 2016)
Abstract This research mainly uses statistical data published by the United Nations Office on Drugs and Crime (UNDDC) in April 2014 to support the hypothesis of this research that â€œHuman Rights Activists in Indonesia as in other countries have failed in comprehending the wisdom (hikmah) of the application of Capital Punishmentâ€. This study found that: (1) the hypothesis of this research was strongly supported by the data; (2) the application of Syari`ah Criminal Law in Saudi Arabia has been an unchallenged proof for the wisdom (hikmah) behind the application of Capital Punishment by keeping the level of murder crime to a low rate which sharply contrast to many countries which apply positive laws which are based on a social contract between the ruler and the ruled, such as in The United States and Mexico; and (3) In upholding the true justice in Islamic Criminal Law, punishment can only be awarded to the criminals in a society where the Islamic ideal of social justice has been achieved. Â Abstrak Penelitian ini menggunakan data statistik yang diterbitkan oleh United Nations Office on Drugs and Crime (UNDDC) pada bulan April 2014 untuk mendukung hipotesis dari penelitian ini bahwa "Aktivis HAM di Indonesia seperti di negara-negara lain telah gagal dalam memahami hikmah dari penerapan hukuman mati". Studi ini menemukan bahwa: (1) hipotesis penelitian ini sangat didukung oleh data; (2) penerapan Hukum Pidana Syari`ah di Arab Saudi telah menjadi bukti tak terbantahkan untuk menunjukkan hikmah di balik penerapan hukuman mati dengan menjaga tingkat kejahatan pembunuhan pada tingkat yang sangat rendah yang sangat berlawanan dengan yang terjadi di banyak negara yang menerapkan hukum positif yang didasarkan pada kontrak sosial antara penguasa dan rakyat, seperti di Amerika Serikat dan Meksiko; dan (3) dalam menegakkan keadilan sejati dalam Hukum Pidana Islam, hukuman hanya dapat diberikan kepada penjahat dalam masyarakat di mana keadilan sosial yang ideal menurut Islam telah dicapai.